UPAYA MENINGKATKAN PERCAYA DIRI SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMA NEGERI 1 SUNGKAI UTARA LAMPUNG UTARA - Pranoto, Hadi (LPPM UM Metro, 2016)
The goals to be achieved by the researchers is to know the results of the implementation of group guidance services in order to increase the confidence of students X.7 SMA Negeri 1 North Sungkai. The research was an action research applied in the service of BK then called (PTL) consisting of two cycles, with each cycle consisting of two meetings. This study was conducted at X.7 class consist of 10 students. The collecting data method used observation and field notes. Researchers define of success criteria 75% in accordance with Government Regulation (PP) No. 19 In 2005, the National Education Standards. This study used data analysis techniques of quantitative and qualitative. The conclusions of this research is through group guidance services can increase the confidence of students, its seen from the results of studies showing that (1) through the Group Guidance service is able to increase confidence of students amounted to 48.75% (the first cycle an average aspect self-confidence by 27.5% and an average second cycle aspects of confidence 76.25%). (2) Guidance services through group-confidence of students can be increased from the first cycle to the second cycle in which the student is considered complete if it has reached the number ≥ 8 students.